Creating 3D Scenarios with OGRE Creativity Labs - Sampaio, Paulo Maia; Teixeira, Duarte Ornelas; Fernandes, Duarte (Journal on Interactive Systems, 2013)
<!– @font-face font-family: "SimSun"; p.MsoNormal, li.MsoNormal, div.MsoNormal margin: 0cm 0cm 0.0001pt; text-align: center; font-size: 10pt; font-family: "Times New Roman"; div.Section1 page: Section1; –> Currently, there are several languages and tools to provide the creation of virtual scenarios. However, the existing approaches are not intuitive and require further knowledge of the user. This paper introduces an application to allow the creation of virtual scenarios with high graphical quality called OGRE Creativity Labs (OGRE-CL). OGRE-CL provides OGRE application developers with a graphical environment for the rapid prototyping of 3D scenarios, and the subsequent automatic generation of the respective OGRE code. With this tool, developers can have their development time optimized since they rather focus on the codification of the dynamics and strategies of the application being developed without spending much time with the design of its graphical components.